Serum tumor necrosis factor-alpha concentrations are negatively correlated with serum 25(OH)D concentrations in healthy women - Heffernan Mary E; Peterson Catherine A (BMC, 2008)
Abstract Background Circulating 25 hydroxyvitamin D (25 (OH)D), an accurate measure of vitamin D status, is markedly greater in individuals with increased exposure to ultraviolet B (UVB) light via sunlight or the use of artificial UV light. Aside from the known relationship between vitamin D and bone, vitamin D has also been implicated in immune function and inflammation. Furthermore, a mass of evidence is accumulating that vitamin D deficiency could lead to immune malfunction. Our overall objective was to study the relationship between vitamin D status (as determined by serum 25(OH) D concentrations) and inflammatory markers in healthy women. Methods This observational study included 69 healthy women, age 25-82 years. Women with high UVB exposure and women with minimal UVB exposure were specifically recruited to obtain a wide-range of serum 25(OH)D concentrations. Health, sun exposure and habitual dietary intake information were obtained from all subjects. Body composition was determined by dual-energy-x-ray absorptiometry. A fasting blood sample was collected in the morning and analyzed for serum 25(OH)D, parathyroid hormone (iPTH), estradiol (E2), cortisol, and inflammatory markers [tumor necrosis factor -alpha (TNF-α), interleukin-6 and -10 (IL-6, IL-10), and C-reactive protein (CRP)]. Results Women with regular UVB exposure (Hi-D) had serum 25(OH)D concentrations that were significantly higher (p < 0.0001) and iPTH concentrations that were significantly lower (p < 0.0001) than women without regular UVB exposure (Lo-D). Although IL-6, IL-10, and CRP did not have a statistically significant relationship with 25(OH)D concentrations, linear regression models revealed a significant inverse relationship between serum 25(OH)D and TNF-α concentrations. This relationship remained significant after controlling for potential covariates such as body fat mass, menopausal status, age, or hormonal contraceptive use. Conclusion Serum 25(OH)D status is inversely related to TNF-α concentrations in healthy women, which may in part explain this vitamin's role in the prevention and treatment of inflammatory diseases. Results gleaned from this investigation also support the need to re-examine the biological basis for determining optimal vitamin D status.